2018
DOI: 10.1021/jacs.8b08050
|View full text |Cite
|
Sign up to set email alerts
|

Probing Antibody Binding to Canine Parvovirus with Charge Detection Mass Spectrometry

Abstract: There are many techniques for monitoring and measuring the interactions between proteins and ligands. Most of these techniques are ensemble methods that can provide association constants and in some cases stoichiometry. Here we use charge detection mass spectrometry (CDMS), a single particle technique, to probe the interactions of antigen binding fragments (Fabs) from a series of antibodies with the canine parvovirus (CPV) capsid. In addition to providing the average number of bound Fabs as a function of Fab c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…The binding and occupancy of Fabs on parvovirus have also been determined previously using charge detection mass spectrometry (CDMS), which revealed that some of the tested monoclonal antibody-derived Fabs, including Fab 14, could fully occupy all 60 epitopes of the capsid, but with some differences in the kinetics of attachment (20). Incubating with excess Fab molecules to occupy all icosahedrally-equivalent sites on capsids has long been the preferred cryo-EM structural approach since this allows icosahedral symmetry averaging to be imposed during the reconstruction process for maximizing resolution (19,21,22).…”
Section: Introductionmentioning
confidence: 76%
“…The binding and occupancy of Fabs on parvovirus have also been determined previously using charge detection mass spectrometry (CDMS), which revealed that some of the tested monoclonal antibody-derived Fabs, including Fab 14, could fully occupy all 60 epitopes of the capsid, but with some differences in the kinetics of attachment (20). Incubating with excess Fab molecules to occupy all icosahedrally-equivalent sites on capsids has long been the preferred cryo-EM structural approach since this allows icosahedral symmetry averaging to be imposed during the reconstruction process for maximizing resolution (19,21,22).…”
Section: Introductionmentioning
confidence: 76%
“…The binding and occupancy of Fabs on the CPV capsid have also been determined previously using charge detection mass spectrometry, which revealed that some of the tested monoclonal antibody–derived Fabs, including Fab 14, could fully occupy all 60 epitopes of the capsid but with some differences in the kinetics of attachment ( 24 ). Incubating with excess Fab molecules to occupy all icosahedrally equivalent sites on capsids has long been the preferred cryo-EM structural approach since this allows icosahedral symmetry averaging to be imposed during the reconstruction process for maximizing resolution ( 18 , 25 , 26 ).…”
mentioning
confidence: 80%
“…Up to now, traditional virus detection techniques include serological assay, mass spectrometry, and surface plasmon resonance (SPR) . However, those traditional methods are time‐consuming, laborious, less sensitive, which limit their clinical applications.…”
Section: Methodsmentioning
confidence: 99%